2008
DOI: 10.1111/j.1600-0854.2008.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Apical Cargo Traverses Endosomal Compartments on the Passage to the Cell Surface

Abstract: Epithelial polarity is based on intracellular sorting machinery that maintains the asymmetric distribution of lipids and proteins to the cell surface. Dependent on their lipid raft affinity, newly synthesized apical polypeptides are segregated into distinct vesicle populations subsequent to the passage through the Golgi apparatus. Using a combined fluorescence microscopic and biochemical approach, we found that lipid raft-associated sucrase-isomaltase (SI) as well as non-raft-associated lactase-phlorizin hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 60 publications
(80 reference statements)
2
48
0
Order By: Relevance
“…Fluorescence and pulse-chase analysis detected the passage of two newly synthesized PM proteins, lactase-phlorizin hydrolase and sucrase-isomaltase, successively through Rab4-, Rab8-and Rab11-positive endosomes. Their transport was inhibited by RNA interference against these Rabs, suggesting that these proteins reach the AEE/ASE first after leaving the TGN (Cramm-Behrens et al, 2008). Route 2 is probably used by rhodopsin, the major component of the outer segments of retinal photoreceptors, which constitute an enlarged version of the primary cilium that is present in most vertebrate cells (Singla and Reiter, 2006).…”
Section: Apical Trafficking Routesmentioning
confidence: 99%
“…Fluorescence and pulse-chase analysis detected the passage of two newly synthesized PM proteins, lactase-phlorizin hydrolase and sucrase-isomaltase, successively through Rab4-, Rab8-and Rab11-positive endosomes. Their transport was inhibited by RNA interference against these Rabs, suggesting that these proteins reach the AEE/ASE first after leaving the TGN (Cramm-Behrens et al, 2008). Route 2 is probably used by rhodopsin, the major component of the outer segments of retinal photoreceptors, which constitute an enlarged version of the primary cilium that is present in most vertebrate cells (Singla and Reiter, 2006).…”
Section: Apical Trafficking Routesmentioning
confidence: 99%
“…In polarized epithelial cells, Rab11a and Rab8a subsume roles more specific to trafficking to the apical membrane (16). Therefore, we examined the dependence of Myo5B on interaction with Rab8a or Rab11a in polarized cells using 3D MDCK cyst cultures.…”
Section: Mutations In Myo5b Independently Affect Localization Of Eithermentioning
confidence: 99%
“…In the case of the disaccharidases lactase phlorizin hydrolase and sucrase isomaltase-a raftdependent protein and raft-independent protein, respectively-separation does not occur immediately after release from the TGN, but rather after sequential movement through Rab4-, Rab8-, and Rab11-positive endosomal compartments (or perhaps subcompartments). 100 Mounting evidence demonstrates that, in addition to being separated into different endosomal compartments, cargoes are segregated into different subdomains within endosomes and that this lateral segregation facilitates cargo sorting (reviewed by Miaczynska and Zerial 101 ). Using immuno-electron microscopy, Sonnichsen et al demonstrated separation of resident Rab GTPases into distinct endosomal subdomains.…”
Section: Sorting Through Endosomesmentioning
confidence: 99%
“…99,167 Conversely, lactase phlorizin hydrolase and sucrase isomalatase traffic between the apical early and apical recycling endosomes (6). 100 Proteins internalized from the apical membrane to the AEE can traffic to the ARE for recycling back to the surface, or to the CRE and late endosomes if they are targeted for degradation (unlabeled arrows). LE, late endosome; lys, lysosome; MVB, multivesicular body.…”
Section: Sorting Through Endosomesmentioning
confidence: 99%